Chemistry the molecular science - Moore, John W. (Thomson Brooks/Cole, 2008)
The most successful first edition General Chemistry text published in the last decade, CHEMISTRY: THE MOLECULAR SCIENCE continues in this new edition to emphasize the traditional core concepts covered in the general chemistry course. Lauded for its focus on visualization for understanding in support of students' conceptual development and its dedicated emphasis on content mastery through a proven problem-solving methodology that actively engages students in the chemical thought process, this Second Edition offers a complete pedagogical solution. The text's student focus is extended through General ChemistryNow--the first assessment-centered Web-based learning tool for general chemistry. Developed in concert, the unparalleled integration of text and media provides students with a seamless learning system. Based on extensive user and reviewer feedback, the Second Edition has been significantly revised to meet the content and organizational needs of today's general chemistry classroom.